Sistem Kendali Suhu dan Kelembapan Pada Alat Pengering Biji Kopi Berbasis Mikrokontroler ESP32 - Gelegar Pilpres Oktavois; Budi Gunawan (Jurnal Ilmiah Global Education, 2026)
This research aims to design and develop an ESP32 microcontroller-based coffee bean drying control system to enhance efficiency and quality compared to traditional sun-drying methods. Conventional methods suffer from several drawbacks, including weather dependency, long drying durations, and a lack of temperature and humidity control, which can potentially degrade the quality of the coffee beans. The study employs the Research and Development (R&D) method, covering the stages of design, construction, and system testing. The system is equipped with a DHT22 sensor to measure temperature and humidity, and a capacitive soil moisture sensor to detect the moisture content of the coffee beans. An on-off control method is implemented using heaters and fans as actuators, managed via relays. Sensor data is displayed on an LCD and can be monitored in real-time. The test results indicate that the drying system functions as planned. In a trial using 3 kg of coffee beans, the system successfully reduced the initial moisture content from 55% to 12% within 3.5 days. The temperature control system exhibited a slow but stable response; the heater activates when the temperature drops below 60°C and deactivates when it exceeds 60°C. Similarly, the humidity control system activates the exhaust fan when humidity exceeds 60% and turns it off when it falls below 55%. This humidity control showed a rapid initial response that decelerated toward the end, with the system exhibiting lower stability compared to the temperature control.